Intestinal epithelial cells related lncRNA and mRNA expression profiles in dextran sulphate sodium‐induced colitis. Issue 2 (9th December 2020) - Liu, Huan; Li, Teming; Zhong, Shizhen; Yu, Min; Huang, Wenhua
Abstract: Intestinal epithelial barrier damage caused by intestinal epithelial cells (IECs) dysfunction plays a crucial role in the pathogenesis and development of inflammatory bowel disease (IBD). Recently, some studies have suggested the emerging role of long non‐coding RNAs (lncRNAs) in IBD. The aim of this study was to reveal lncRNAs and mRNA expression profiles in IECs from a mouse model of colitis and to expand our understanding in the intestinal epithelial barrier regulation. IECs from the colons of wild‐type mice and dextran sulphate sodium (DSS)‐induced mice were isolated for high‐throughput RNA‐sequencing. A total of 254 up‐regulated and 1013 down‐regulated mRNAs and 542 up‐regulated and 766 down‐regulated lncRNAs were detected in the DSS group compared with the Control group. Four mRNAs and six lncRNAs were validated by real‐time quantitative PCR. Function analysis showed that dysregulated mRNAs participated in TLR7 signalling pathway, IL‐1 receptor activity, BMP receptor binding and IL‐17 signalling pathway. Furthermore, the possibility of indirect interactions between differentially expressed mRNAs and lncRNAs was illustrated by the competing endogenous RNA (ceRNA) network. LncRNA ENSMUST00000128026 was predicted to bind to mmu‐miR‐6899‐3p, regulating Dnmbp expression. LncRNA NONMMUT143162.1 was predicted to competitively bind to mmu‐miR‐6899‐3p, regulating Tnip3 expression. Finally, the protein‐protein interaction (PPI) network analysis was constructed with 311 nodes and 563 edges. And the highest connectivity degrees were Mmp9, Fpr2 and Ccl3. These results provide novel insights into the functions of lncRNAs and mRNAs involved in the regulation of the intestinal epithelial barrier.